A272 THE CANADIAN DIRECT OBSERVATION OF PROCEDURAL SKILLS (CANDOPS) TOOL FOR ENDOSCOPIC RETROGRADE CHOLANGIOPANCREATOGRAPHY: A MULTI-CENTRE PROSPECTIVE STUDY. (26th February 2020) - Khan, U; Barkun, A N; Benchimol, E I; Salim, M; Telford, J J; Enns, R A; Mohamed, R; Forbes, N; Sandha, G S; Mosko, J; May, G; Kortan, P; et al.
Abstract: Background: Previous studies have demonstrated that many graduating trainees may not have all of the skills needed to independently practice endoscopic retrograde cholangiopancreatography (ERCP) safely and effectively. As a part of competency-based learning curriculum development, it is essential to provide formative feedback to trainees and ensure they acquire the knowledge and skills for independent practice. Aims: To assess the performance of advanced endoscopy trainees across Canada using the Canadian Direct Observation of Procedural Skills (CanDOPS) ERCP assessment tool. Procedural items evaluated include both technical (cannulation, sphincterotomy, stone extraction, tissue sampling, and stent placement) and non-technical (leadership, communication and teamwork, judgment and decision making) skills. Methods: We conducted a prospective national multi-centre prospective study. Advanced endoscopy trainees with at least two years of gastroenterology training or five years of general surgery in North America and minimal experience performing ERCPs (less than 100 ERCP procedures) were invited to participate. The CanDOPS tool was used to measure every fifth ERCP performed by trainees over a 12-month fellowship training period. ERCPs were evaluated by experienced staff endoscopists at each study site under standard clinical protocol. Cumulative sum (CUSUM) analyses were used to generate learning curves. Results: The data from five Canadian sites and 11 trainees participated in the study. A total of 261ERCP evaluations were completed. Median number of evaluations by site and trainee was 49 (IQR 31–76) and 15 (IQR 11–45). Median number of cases trainees performed prior to their ERCP training was 50 (IQR 25–400). There was a significant improvement in almost all scores over time, including selective cannulation, sphincterotomy, biliary stenting and all non-technical skills (P<0.01). CUSUM analyses using acceptable and unacceptable failure rates of 20% and 50% demonstrated trainees achieved competency for most measures in their final month of their training. Competency in tissue sampling was not achieved within a one-year training period. Conclusions: This is the first ERCP performance evaluation tool that examines multiple technical and non-technical aspects of the procedure. Although trainee ERCP skills do improve during their training period, there exists a notable variability in time to competency for the different skills measured using the CanDOPS tool. Large prospective research is required to determine if competency is achieved using more stringent definitions of ERCP competency and to determine factors associated with reaching competency. Funding Agencies: None